2023
DOI: 10.1002/ehf2.14300
|View full text |Cite
|
Sign up to set email alerts
|

Omecamtiv mecarbil augments cardiomyocyte contractile activity both at resting and systolic Ca2+ levels

Abstract: Aims Heart failure with reduced ejection fraction (HFrEF) is a disease with high mortality and morbidity. Recent positive inotropic drug developments focused on cardiac myofilaments, that is, direct activators of the myosin molecule and Ca 2+ sensitizers for patients with advanced HFrEF. Omecamtiv mecarbil (OM) is the first direct myosin activator with promising results in clinical studies. Here, we aimed to elucidate the cellular mechanisms of the positive inotropic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These findings are consistent with previous studies that showed little or no effect of OM on cytosolic Ca 2+ transients [3,33]. However, other studies have reported that OM is capable of prolonging the duration of the contractile force or Ca 2+ transients in isolated human atrium or heart cells, despite no change in the contractile force [34,35]. Therefore, further investigation is necessary to determine the extent to which OM-induced prolongation of the contractile duration of cardiac muscle is due to its preferential stimulation of I Na(L) [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies that showed little or no effect of OM on cytosolic Ca 2+ transients [3,33]. However, other studies have reported that OM is capable of prolonging the duration of the contractile force or Ca 2+ transients in isolated human atrium or heart cells, despite no change in the contractile force [34,35]. Therefore, further investigation is necessary to determine the extent to which OM-induced prolongation of the contractile duration of cardiac muscle is due to its preferential stimulation of I Na(L) [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 92%
“…From this aspect, OM is indeed much superior to these drugs for its Ca2+ level-independent effects in cardiac contractile enhancement. This was proven in in-vitro experiments by Ráduly et al in cardiomyocytes isolated from dogs with entire cell membranes ( 27 ). Upon their experiments, regardless of the distinct difference in intracellular Ca2+ concentrations at systolic and resting states, OM remained intensively functional in strengthening cardiac contractility.…”
Section: The Rationale Of Drug Therapy In Heart Failurementioning
confidence: 76%
“…The binding pocket is available only when the lever arm is primed. Fundamentally, OM augments the myosin heads primed to bind to the actin filament, thus producing an increased contraction force soon after the binding between Ca 2+ and troponin-tropomyosin complex [30][31][32]. Moreover, OM is responsible for the slowing of the non-productive turnover of ATP, thus reducing the use of ATP not associated with mechanical work [30].…”
Section: Innovative Pharmacological Targets In Worsening Heart Failurementioning
confidence: 99%
“…The latter occurs early on and is itself potentially able to perpetuate myocardial injury and loss of cardiomyocytes. OM could block this negative feedback cycle by acting directly on the systolic function, thus preventing cardiac remodelling and activation of the neurohormonal system [30][31][32]. Importantly, no relevant adverse effects regarding increase in heart rate, blood pressure or myocardial oxygen consumption have been highlighted [30][31][32] (Figure 4).…”
Section: Innovative Pharmacological Targets In Worsening Heart Failurementioning
confidence: 99%
See 1 more Smart Citation